Model law on competition : draft commentaries to possible elements for articles of a model law or laws (UN GenevaCH, 2000)
Contains a revised version of the draft possible elements for articles as contained in Part I of the document 'Draft commentaries to possible elements for article of a model law or laws' (TD/B/RBP/81/Rev.5), and includes a revised version of the commentary to articles which was contained in Part II of TD/B/RBP/81/Rev.5, taking into account recent trends in competition legislation adopted worldwide.
Keywords: COMPETITION